Evaluasi Pengalaman Belajar Mahasiswa Dalam Penggunaan Kamus Digital Jamak Taksir Pada Pembelajaran Kitabah - Joni Kawijaya; Lukman Habibul Umam; Mulyono (Jurnal Adab dan Peradaban Islam, 2026)
The utilization of digital technology in Arabic language learning, particularly digital dictionaries for jamak taksir (broken plurals), significantly depends on user experience (UX). This study aims to evaluate students' learning experiences using a jamak taksir digital dictionary in kitabah (writing) instruction at IAI Darul A’mal Lampung. Employing a descriptive quantitative approach, data were collected from 10 students via Likert-scale questionnaires and observations, then analyzed using SPSS. The results indicate that the user experience falls into the "Excellent" category, with an average score of 4.28 (85.6%). Specific scores include user satisfaction (4.35) and usefulness (4.40). Students found it easier to adapt, felt supported during the writing process, and showed increased confidence. Despite obstacles such as limited interactive features and varying digital literacy, these findings prove that UX is vital for effective learning media. Consequently, future digital media development must comprehensively consider user experience to enhance the quality of Arabic language pedagogy in religious higher education.